2010
DOI: 10.12968/bjcn.2010.15.7.48774
|View full text |Cite
|
Sign up to set email alerts
|

District nurses prescribing as nurse independent prescribers

Abstract: Nurse prescribing has been established in the UK since 1994, however, limited focus has been placed on the experiences of district nurses adopting this additional role. This phenomenological study explores the experiences of district nurses prescribing as nurse independent prescribers across the West of Scotland. A qualitative Heideggarian approach examined the every-day experiences of independent prescribing among district nurses. A purposive sample was used and data collected using audio taped one-to-one inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(82 citation statements)
references
References 21 publications
5
77
0
Order By: Relevance
“…Of the 17 studies nine considered questions of efficiency; seven of them as a part of a broader study and two considered only questions of efficiency using qualitative [42,45] and quantitative [58] methods. All these studies reported prescribing by nurses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 17 studies nine considered questions of efficiency; seven of them as a part of a broader study and two considered only questions of efficiency using qualitative [42,45] and quantitative [58] methods. All these studies reported prescribing by nurses.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies of nurses' views reported that being able to prescribe enabled them to provide seamless and patient centred care [45,46]. A UK based observational survey of clinical accounts reported that nurse prescribers fully completed the episode of care, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…They could also work more effectively and use resources in the best way possible, which harmonized with the researchers' view that good collaboration with physicians is an important factor for co-operation and job satisfaction. 32,[36][37][38] Nurses' professional role also includes knowledge of the patient's diagnosis and treatment, and the ability to make their own judgments and act upon them. 39 This discussion harmonizes with the present study that describes nurses' need for time and opportunities to practice advanced care to prepare for a demanding home health care.…”
Section: Discussionmentioning
confidence: 99%
“…Some UK studies have suggested nurses’ lack of employer support [30,59] and there is a need for change champions in local health care systems [60], however these were nurses who had employer support as evidenced by the employer registering them as prescribers with the ePACT database. It raises questions as to why such numbers of nurses have gained the prescribing qualification for it then not to be used in practice.…”
Section: Discussionmentioning
confidence: 99%
“…It raises questions as to why such numbers of nurses have gained the prescribing qualification for it then not to be used in practice. One hypothesis, derived from the literature [30,59] and requiring testing, is that nurses who have access to a clinical mentor or supervisor are more likely to prescribe than those who no or little access. A second hypothesis that requires further investigation is that the ambivalence to this role is more wide spread amongst primary care nurses than previously reported and they are choosing not to prescribe and as such acting as ‘ street - level bureaucrats ’ [61] i.e.…”
Section: Discussionmentioning
confidence: 99%